NT-3/TrkC Axis Contributes to the Perineural Invasion and the Poor Prognosis in Human Salivary Adenoid Cystic Carcinoma - Li, Huan (J Cancer, 2019)
The present study was aimed to investigate the role and mechanism of neurotrophin-3 (NT-3) and its specific receptor tropomyosin receptor kinase C (TrkC) in the perineural invasion (PNI) process of the salivary adenoid cystic carcinoma (SACC). The co-cultured system between SACC cells and Schwann cells (SCs) was employed to detect the expression of NT-3 and TrkC. The results of ELISA, qRT-PCR and western blot showed that NT-3 was noticeably elevated in the co-cultured SACC-83 cells, while TrkC was increased in the co-cultured SCs. The results of scratch wound healing, migration, and 3D co-culture assays showed that the directional migration abilities of the co-cultured SACC-83 cells and SCs were significantly increased. Under the stimulation of NT-3, the directional motor ability of SACC-83 cells and SCs was significantly improved, and the apoptosis of SACC-83 cells and SCs were obviously inhibited. In addition, blocking TrkC by its specific inhibitor AZD7451 could significantly inhibit these effects. Immunohistochemistry staining showed that the positive expression of NT-3 (88.5%) and TrkC (92.3%) was significantly correlated with the PNI in SACC specimens (P < 0.05). Additionally, the high expression of NT-3 was significantly associated with the poor prognosis of SACC patients (P < 0.05). The present study indicated that NT-3/TrkC axis contributed to the PNI progression and the poor prognosis of SACC via regulating the interaction between SACC cells and SCs. Interruption of the interaction between SACC cells and SCs by blocking the NT-3/TrkC axis might be an effective strategy for anti-PNI therapy in SACC.